Study of changes in serum iron, albumin and calcium levels in smear positive pulmonary tuberculosis patients compared with healthy individuals before starting Directly Observed Treatment, Short course - Biswas, Prithwy Shankar; Tuli, Jesmin Zahan; Ruba, Rubayea Afrin; Rahman, Tasnim; Hasanat, Farzana; Azad, Afroza (Mediscope, 2022)
Background: Tuberculosis one of the most important infectious diseases throughout the world. Bangladesh is a highly populated country and a significant amount of mortality and morbidity is caused by tuberculosis, especially pulmonary tuberculosis. Objectives: To evaluate the levels of serum iron, albumin and calcium in smear positive pulmonary tuberculosis (PTB) patients before starting Directly Observed Treatment, Short course (DOTS) regimen. Methods: This was a cross-sectional study. A total of 100 subjects were included in this study. Among them, 50 were smear positive PTB patients denoted as case group and 50 were apparently healthy individuals denoted as control group. Biochemical tests were carried out in the Department of Biochemistry, Mymensingh Medical College. All the statistical analyses were performed by SPSS version 21. Results were evaluated by using Student’s t-test. Results: The study revealed that mean values of serum iron were 128.24±13.20 μg/dl and 86.13±24.56 μg/dl in control and case group respectively, and the difference between two groups were highly significant (p <0.001). The mean serum albumin level was lower in case group when compared to control group. The mean values of serum albumin were 4.1±0.33 gm/dl and 3.5±0.31 gm/dl in control and case group respectively, and the difference between two groups were highly significant (p <0.001). The mean values of serum calcium were 2.33±0.19 mmol/L and 2.5±0.16 mmol/L in control group and case group respectively. Serum calcium level was adjusted by serum albumin concentration. The analysis showed that, the difference in mean serum calcium levels between two groups were highly significant (p <0.001) Mediscope 2022;9(1): 25-29